Corporate social responsibility in Central Asia: A comparative analysis (Вестник КазНУ. Серия Экономическая, 2016)
Social responsibility of business is an important component of sus-tainable development of any country. Central Asian countries have just begun to take first steps in this direction. The purpose of this study is to investigate and identify the peculiarities of CSRdevelopment in five Cen-tral Asian countries: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. The main research method used in the study relies on a com-parative analysis of social initiatives in these counties within the frame-work suggested by Carroll. The results suggest that the concept of CSR in Central Asia is still developing and there are many uncertainties associated with the interpretation of the term. Most companies in the region focus on one-off charity events which is indicative of the predominance of Carroll’s philanthropic responsibility in the region. Additionally, there is a lack of incentives for promoting CSR among companies operating in Central Asia.
Keywords: corporate social responsibility; Carroll’s pyramid; business; Central Asian region